The relationship between COVID-19-related restrictions and fear of missing out, problematic smartphone use, and mental health in college students: The moderated moderation effect of resilience and social support - Gong, Zhun; Lv, Yun; Jiao, Xinian; Liu, Jinhang; Sun, Yingjie; Qu, Qunzhen (Frontiers in Public Health, 2022)
As one of the groups most affected by the epidemic, the mental health of college students during the epidemic is a focus of attention in multiple fields. Based on resource conservation theory, this study investigates the impact of COVID-19-related restrictions on college students’ problematic smartphone use and mental health from two perspectives, students’ individual factors and external environmental factors, and specifically explores the role of fear of missing out (FoMO), resilience and social support in this context. This study used a questionnaire method, and to control for common method bias, a multitemporal data collection strategy was used. The study used online questionnaire distribution, the final sample included 975 Chinese college students (497 males and 478 females), and of these, 10.3% were freshmen, 31.9% were sophomores, 31.6% were juniors, 12.3% were seniors, and 13.9% were postgraduates. The results of this study showed the following: (1) Perceived COVID-19-related strain was positively correlated with perceived FoMO, problematic smartphone use and mental health problems (depression, anxiety, stress) among college students. (2) FoMO partially mediated the relationship between perceived COVID-19-related restrictions and problematic smartphone use, and it fully mediated the relationship between perceived COVID-19-related restrictions and mental health problems. (3) Resilience and social support co-moderated the relationship between FoMO and problematic smartphone use or mental health problems (depression, anxiety, stress).